2016
DOI: 10.1155/2016/2565169
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Shenfu Injection in the Treatment of Septic Shock Patients: A Multicenter, Controlled, Randomized, Open‐Label Trial

Abstract: The effect of Shenfu on biochemical parameters and survival during resuscitation in patients with septic shock was examined. This was a multicenter, controlled, randomized, open-label trial carried out in 210 patients with septic shock from seven medical centers in China. They were randomized to Shenfu or saline. The primary outcome was lactate clearance. The secondary outcomes were shock index normalization, dose of vasopressors, ICU stay, hospital stay, and mortality. A total of 199 patients completed the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Nevertheless, it should be noted that commercial SF preparation was used in this study. It has been recognized that aconitum alkaloids and ginsenosides are the main active components in SF preparation [13, 14]. Yang et al identified 23 trace diterpene alkaloids, 19 ginseng saponins, one panaxytriol, and one 5-hydroxymethylfurfural in SF preparation, and quantitated that the total concentrations of saponins and alkaloids were about 676 – 742 µg/mL and 3 – 7 µg/mL in five batches of SF preparation samples, respectively [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it should be noted that commercial SF preparation was used in this study. It has been recognized that aconitum alkaloids and ginsenosides are the main active components in SF preparation [13, 14]. Yang et al identified 23 trace diterpene alkaloids, 19 ginseng saponins, one panaxytriol, and one 5-hydroxymethylfurfural in SF preparation, and quantitated that the total concentrations of saponins and alkaloids were about 676 – 742 µg/mL and 3 – 7 µg/mL in five batches of SF preparation samples, respectively [13].…”
Section: Resultsmentioning
confidence: 99%
“…SF preparation is prepared by using countercurrent extraction and macroporous resin adsorption chromatography. In China, SF preparation is commonly used in clinical practice for the treatment of septic shock and ischemic diseases and has been shown to have a beneficial role against ischemic-reperfusion injuries on many organs including the brain, spinal cord, kidneys, intestines, liver and heart [14, 15]. Recently, it was reported that SF preparation has obviously protective effects on cardiomyocytes against apoptosis by inhibition of down-regulation of Bcl-2 and sequential activation of caspase 3 [15].…”
Section: Introductionmentioning
confidence: 99%
“…In China, although there have been many clinical trial reported the efficacy of Shenfu injection in shock, there are still some problems in these trials, such as small sample size and low methodological quality. [ 34 ] Also, Correcting microcirculation disorders plays a vital role in the prognosis of shock patients. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[9] Although there have been many clinical trials reporting SFI's curative effect in septic shock in China, there are still some problems in these trials such as small sample sizes and low methodological quality. [10] For this reason, the objective of our study is to carry out a meta-analysis to evaluate its clinical efficacy and safety in septic shock patients and we expect that our study could provide a reference for further clinical practice.…”
Section: Introductionmentioning
confidence: 99%